Personal thermal comfort models using digital twins: Preference prediction with BIM-extracted spatial-temporal proximity data from Build2Vec - Abdelrahman, Mahmoud M (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
10.1016/j.buildenv.2021.108532